Marine impacts caused by technological advances of Offshore power plants in Brazil and possible environmental damage - Junior, Alcides Miguel da Silva; Cunha, Fernanda Nathália Carneiro da; Costa, Itamar Victor de Lima; Monteiro, Eliana Cristina Barreto; Takaki , Galba Maria Campos (Seven Editora, 2023)
Offshore wind power plants have been growing worldwide, with 2021 being a historic year for this modality, considering that energy from renewable sources strongly contributes to a more sustainable future. China is the country with the largest number of plants of this type along with Brazil having the highest energy potential. However, Brazil does not yet have any plant in operation. However, the prediction of the serial impacts that may exist that can be generated from the implementation phase to the deactivation phase, but there are no conclusive studies regarding the damage caused to the unique marine ecosystems existing in Brazil. In this sense, a review is being presented demonstrating the promising prospects of creating wind power plants related to the existence of 66 projects registered with IBAMA, however, there are still no in-depth studies on the possible environmental impacts. DOI:https://doi.org/10.56238/alookdevelopv1-148